Genetic polymorphisms of platelet receptors in patients with acute myocardial infarction and resistance to antiplatelet therapy - Úlehlová, Jana; Slavík, Luděk; Kučerová, Jana; Krčová, Věra; Václavík, Jan; Indrák, Karel (Genetic testing and molecular biomarkers, 2014)
METHODS: The studied group comprises 124 patients with acute myocardial infarction on dual antiplatelet therapy with acetylsalicylic acid (ASA) and thienopyridines. Antiplatelet therapy was monitored by platelet-rich plasma light transmittance aggregometry (LTA) using the APACT 4004 analyzer (Helena Laboratories) and by whole blood impedance aggregometry (multiple electrode aggregometry [MEA]) using the Multiplate analyzer (Dynabyte). Platelet aggregation was detected after stimulation with arachidonic acid for detection of aspirin resistance and with adenosine diphosphate (ADP) and prostaglandin E1 for detection of thienopyridine resistance. To determine the frequencies of P2Y12 (i-744T>C; rs2046934), P2Y12 (34C>T; rs6785930), COX-1 (-842A>G; rs10306114), GPVI (13254T>C; rs1613662), and GPIbA (5T>C; rs2243093) polymorphisms, DNA of patients with AIM was tested by real-time-polymerase chain reaction and melting curve analysis using the LightCycler 480 analyzer (Roche Diagnostics). RESULTS: The cut-off points used for patients with effective ASA therapy are 25% of aggregated platelets and 220 area under the curve (AUC)/min if LTA or MEA, respectively. The cut-off points used for effective thienopyridine therapy are 45% of aggregated platelets or 298 AUC/min, respectively. Both LTA and MEA found that aspirin and thienopyridine therapies failed in 14.51% and 25.8%, respectively. The data were statistically processed using the SPSS version 15 software (SPSS, Inc.). Associations between receptor mutation status and response to therapy were assessed with Fisher's exact test. The significance level was set at 0.05. CONCLUSION: The aim of our work was to use the two functional laboratory methods described earlier to assess both aspirin and thienopyridine resistance and to determine the contribution of genetic polymorphisms of platelet receptors to resistance to antiplatelet therapy in AIM. Fisher's exact test showed a significant statistical correlation between platelet function tests suitable for monitoring ASA resistance, that is, LTA and MEA, and mutation status of COX1_A1 (-A842G). Fisher's exact test showed no statistically significant correlations between platelet function tests suitable for monitoring ASA resistance, that is, LTA and MEA, and mutation status of GP1bA (-5T>C) and GP6 (T13254C). Fisher's exact test showed no statistically significant correlation between mutational statuses of the receptors P2RY12 (i-T744C), P2RY12 (C34T), GP1bA (-5T>C), or GP6 (T13254C) and response to antiplatelet therapy with 75 mg of clopidogrel.
Keywords: dospělí; Drug Resistance; Female; Adult; ženské pohlaví; léková rezistence; lidé; antigeny trombocytů; Pilot Projects; Platelet Aggregation Inhibitors; Antigens, Human Platelet; pilotní projekty; Aged, 80 and over; Male; Point Mutation; Aged; polymorfismus genetický; bodová mutace; Myocardial Infarction; inhibitory agregace trombocytů; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Polymorphism, Genetic; Middle Aged; infarkt myokardu; Humans